Peran Guru Dalam Melatih Kemandirian Anak Autism Dengan Metode Pembiasaan Di TK Sinar Indonesia Bekasi - Pratiwi , Nadyah Dwi; A.E , Yon; Priyanti , Nina Yuminar (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The Role of Teachers in Training the Independence of Children with Autism with Habituation Methods at Kindergarten Sinar Indonesia Bekasi (2024). Thesis. Jakarta: Panca Sakti College of Teacher Training and Education, Bekasi. 2024.This study aims to test the role of teachers in training the independence of children with autism in Kindergarten Sinar Indonesia Bekasi, using an instrument of independence development with the role of teachers in training the independence of children with autism and the use of habituation methods in stimulating the development of children's independence using the form of the Likert model attitude scale.The research method used is a descriptive research method with a qualitative approach. The subject of this research is an element of the Sinar Indonesia Bekasi Kindergarten institution which includes the Principal, Class Teacher, Accompanying Teacher and one Autism student. Data collection techniques use observation, interviews and documentation with a qualitative data analysis process through several activities, namely data reduction, data display and conclusion drawing/verification The results of the study show that the role of teachers as demonstrators, classroom managers and motivators can train the independence of children with autism in Sinar Indonesia Kindergarten. With the habituation method that is carried out repeatedly on children with autism and also collaboration between the principal, classroom teachers and also companions are all things that can train the independence of children with autism at school, in addition to the process of preparation, implementation and evaluation is a consideration to determine whether the child with autism can be independent or not in his daily life at school.The results of this study provide importance for the development of education, especially related to the role of teachers in training children with autism.